Novel P22-monoclonal antibody based blocking ELISA for the detection of African swine fever virus antibodies in serum - Ghebremedhin Tsegay; Weldu Tesfagaber; Yuanmao Zhu; Xijun He; Wan Wang; Zhenjiang Zhang; Encheng Sun; Jinya Zhang; Yuntao Guan; Fang Li; Renqiang Liu; Zhigao Bu; et al. (Elsevier, 2022)
African swine fever (ASF) is a highly infectious, transboundary viral disease of domestic and wild pigs, and is currently the most serious threat to world swine production, resulting in significant economic loss. In the absence of vaccines and treatments, the control of the disease entirely depends on accurate and early diagnosis accompanied by the culling of infected pigs. Thus, a highly specific and sensitive diagnostic assay is required during an outbreak and surveillance of the disease. In this study, a highly sensitive, specific, rapid and repeatable P22-monoclonal antibody-based blocking enzyme-linked immunosorbent assay (bELISA) assay was developed for the detection of antibodies against genotype I and II African swine fever viruses(ASFVs). A total of 806 pig serum samples were tested to evaluate the performance of the diagnostic assay. To determine the PI (percent Inhibition) cut-off value, receiver-operating characteristic (ROC) analysis was applied. According to the ROC analysis of the data, 98.10% specificity and 100% sensitivity were recorded when the threshold cut-off value of PI was established at 47%. In addition, the assay was able to detect ASFV antibodies as early as 9 days post-infection when serum samples from experimentally infected pigs were used. Taking all together, the results of the present study indicated that the P22-mAb based bELISA assay can be used for rapid and accurate detection of antibodies against ASFV, which could play a valuable role in the containment and prevention of ASFV as an alternative to other serological diagnostic methods. Also, this study will assist researchers to further investigate the immunogenic importance of P22 protein in ASFV infection.